Netnographic Analysis of Public Behavior on Ms Glow Product Advertisement - Evaliata Br. Sembiring; Windy Afriya (SOSHUM : Jurnal Sosial dan Humaniora, 2022)
Ms. Glow is a Skincare and Cosmetic Product, which has expanded its wings in the digital realm. Some of the business strategies implemented: (1) keep interacting online with offline because not all targets can access only one channel; (2)cooperate with as many public figures as possible from micro, macro to mega public figures; (3)live broadcasting of talk show sessions through social media or partners because in this way it can reach a wider target; (4) present in every marketing channel, such as television, radio, print media, displaying billboards in the expansion area or even Videotron. Based on data from the sales inventory, new products and products that are rarely promoted through advertising, have lower sales turnover, when compared to products that are often advertised. This research creates an advertisement video for Ms. Glow's new product, Nail Polish. The research method applied is Research and Development, namely making video ads using the Four D model, and analyzing people's behaviour towards Ms. Glow products using a mixed method, namely through a netnography approach. The results showed that this 58-second video was able to have a positive influence on people's behaviour, namely being interested and even buying the advertised product.